COLLECTIVE CREATIVE EFFICACY AS A MEDIATION OF THE INFLUENCE OF CREATIVE SELF EFFICACY ON STUDENTS’ CREATIVITY: - - Erlina, Merly; Oktaviana, Mistety; Indrawati, Erdina; Diah Nurhadianti, RR. Dini (JP (Jurnal Pendidikan) : Teori dan Praktik, 2024)
The purpose of this study was to investigate the mediating role of creative collective efficacy on the effect of creative self-efficacy on the creativity of a class X student team at SMAN 12 Tangerang Banten. The number of subjects who became the research sample was 122 people. The research method used is a quantitative method. The data analysis technique used by researchers is multiple analysis techniques and indirect effect analysis. The results of the study show that creative self-efficacy influences team creativity. Creative collective efficacy also influences team creativity. The results of the indirect effect analysis show that creative collective efficacy mediates the effect of creative self-efficacy on team creativity in class X students of SMAN 12 Tangerang Banten with a significance value of 0.00000124 <0.005.